2021
DOI: 10.36624/jpkp.v12i2.81
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebijakan Kartu Pra Kerja Dalam Upaya Peningkatan Skill Para Calon Pekerja di Kabupaten Garut

Riksa Raesalat,
Shella Lutfi Alifia

Abstract: Berdasarkan penelitian yang peneliti lakukan mengenai Analisis Kebijakan Kartu Pra kerja Dalam Upaya Peningkatan Skill Para Calon Pekerja Di Kabupaten Garut, peneliti menemukan adanya permasalahan serta manfaat terkait dengan program ini. Tujuan dari penelitian ini yaitu mengetahui analisis kebijakan kartu pra kerja dalam upaya peningkatan skill para calon pekerja di kabupaten Garut. Penelitian ini merupakan penelitian Kualitatif dengan teknik pengumpulan data yang dilakukan dalam penelitian ini adalah wawanca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similarly, Tasmilah (2022) finds that the program impacts entrepreneurship in the service sector but not in other sectors. Findings by Raesalat and Alifia (2021) The sociodemographic conditions in this study depict the population characteristics in an area, explaining social and demographic conditions (Amira & Marhaeni, 2016). Sociodemographic characteristics are crucial in assessing the population's condition in a specific area, providing a comprehensive overview of population characteristics related to individual welfare.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, Tasmilah (2022) finds that the program impacts entrepreneurship in the service sector but not in other sectors. Findings by Raesalat and Alifia (2021) The sociodemographic conditions in this study depict the population characteristics in an area, explaining social and demographic conditions (Amira & Marhaeni, 2016). Sociodemographic characteristics are crucial in assessing the population's condition in a specific area, providing a comprehensive overview of population characteristics related to individual welfare.…”
Section: Introductionmentioning
confidence: 83%
“…Tasmilah (2022) found that the program affected entrepreneurship creation in the service sector but not in other sectors. Raesalat and Alifia (2021) reported that the program had a positive impact, especially for those recently laid off, stimulating them to start new businesses.…”
Section: Impact Of the Pre-employment Card Program On Individual Empl...mentioning
confidence: 99%